Training in innovative technologies for close-range sensing in Alpine terrain - Rutzinger, Martin; Bremer, Magnus; Höfle, Bernhard; Hämmerle, Martin; Lindenbergh, Roderik; Oude Elberink, Sander; Pirotti, Francesco; Scaioni, Marco; Wujanz, Daniel; Zieher, Thomas (ISPRS TC II Mid-term Symposium "Towards Photogrammetry 2020", 2018)
The 2nd international summer school “Close-range sensing techniques in Alpine terrain” was held in July 2017 in Obergurgl, Austria. Participants were trained in selected close-range sensing methods, such as photogrammetry, laser scanning and thermography. The program included keynotes, lectures and hands-on assignments combining field project planning, data acquisition, processing, quality assessment and interpretation. Close-range sensing was applied for different research questions of environmental monitoring in high mountain environments, such as geomorphologic process quantification, natural hazard management and vegetation mapping. The participants completed an online questionnaire evaluating the summer school, its content and organisation, which helps to improve future summer schools.